Airport Passenger Traffic Forecast: An Exploratory Study - Pintanugra Persadanta (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
Sultan Hasanuddin International Airport has been an important hub airport in Indonesia for decades, connecting traffic between west and east Indonesia as well as functioned as international gate in East Indonesia along with Sam Ratulangi Airport. Analysing characteristics of historical traffic data pattern, determining factors affecting past behaviour and building the best-fit model to forecast future traffic are critical for airport operator. Several forecast techniques are employed including Holt-Winter, Decomposition Method and Econometric Model. Moreover, trend, seasonal event and irregular phenomena from past data are observed to analyse traffic behaviour. Passenger traffic data from 1995 up to 2015 is utilized to predict future traffic until 2020. Validation of selected forecast model is conducted by implementing backtesting method which shows that the model successful foretell annual passenger movement with estimation average deviation around 0.5%. Some potential risks and opportunities as well as potential route expansion are identified to fortify future challenges.